Investigation on the influence of structural surface characteristics on stress wave propagation behavior - Jing, Pengxu; Zheng, Wenbo; Wang, Haiying; Wang, Yang; Yang, Haitao (Frontiers in Earth Science, 2025)
When stress waves propagate in rock slopes, they are influenced by various factors such as structural plane characteristics (e.g., stiffness, number, spacing, thickness), sawtooth structural characteristics (e.g., stiffness, angle of sawtooth structural planes), filling materials (fully filled, partially filled, and different filling materials), and wave impedance properties, leading to phenomena such as amplitude attenuation, signal delay, and wave velocity reduction. In this paper, using the one-dimensional Hopkinson bar model as an example, a numerical method is employed to analyze the propagation behavior of stress waves through structural planes with different characteristics. By monitoring key parameters such as permanent displacement, acceleration, and stress values of the stress waves, the influencing laws are revealed: When the stiffness of the structural planes exceeds a certain critical threshold (i.e., 2.8×10⁶ Pa), the permanent displacement, acceleration, and stress values of the stress waves significantly increase with increasing stiffness. The increase in structural plane spacing promotes significant growth in the permanent displacement, acceleration, and stress values of the stress waves, which is another key factor affecting the propagation characteristics of stress waves. Conversely, as the number and thickness of structural planes increase, the response parameters of the stress waves exhibit a decreasing trend, revealing the hindering effect of dense and thickened structural planes on stress wave propagation. An increase in the angle of sawtooth structural planes exacerbates the reflection and attenuation of stress waves, leading to a significant reduction in the peak values of permanent displacement and acceleration, which further emphasizes the influence of structural plane morphology on the propagation path and energy distribution of stress waves. Additionally, the density of filling materials has proven to be a non-negligible factor, as its increase helps reduce energy dissipation, thereby enhancing the propagation effect of stress waves. In cases where there is a significant difference in wave impedance, the amplitude and propagation velocity of stress waves are significantly reduced, highlighting the importance of wave impedance matching in wave propagation. Furthermore, an increase in the damping ratio further accelerates the energy dissipation process, resulting in a significant reduction in the amplitude of stress waves at the propagation endpoint, which emphasizes the crucial role of damping effects in the attenuation of stress wave energy. The research results provide a theoretical basis for the analysis of rock mass dynamic behavior and rock slope stability, and have important guiding significance for the engineering design and disaster prevention of geomaterials under complex geological conditions.